2011 International Conference on Digital Image Computing: Techniques and Applications 2011
DOI: 10.1109/dicta.2011.64
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Shape and Probability Prior Model for Automatic Prostate Segmentation

Abstract: Abstract-Accurate prostate segmentation in Trans RectalUltra Sound (TRUS) images is an important step in different clinical applications. However, the development of computer aided automatic prostate segmentation in TRUS images is a challenging task due to low contrast, heterogeneous intensity distribution inside the prostate region, imaging artifacts like shadow, and speckle. Significant variations in prostate shape, size and contrast between the datasets pose further challenges to achieve an accurate segment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In 2011, Ghose et al [33] presented a new statistical shape model approach using graph cuts in a Bayesian framework for automatic prostate outlining. K-means clustering was used to However, in their methodology, posterior probabilities obtained from MRF modeling were replaced with intensity.…”
Section: Boundary Segmentation Using Graph Cuts (Hybrid Method-2011)mentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, Ghose et al [33] presented a new statistical shape model approach using graph cuts in a Bayesian framework for automatic prostate outlining. K-means clustering was used to However, in their methodology, posterior probabilities obtained from MRF modeling were replaced with intensity.…”
Section: Boundary Segmentation Using Graph Cuts (Hybrid Method-2011)mentioning
confidence: 99%
“…A quantitative comparison of performance evaluation between the reviewed algorithms (given in Chapter 2) and our proposed method is listed in Shen et al [23] 2003 N/A 500 MHz 64 sec Abolmaesumi [24] 2004 512x512 N/A N/A Gong et al [25] 2004 256x256 P4 -2GHz 5 sec Sahba et al [26] 2005 N/A N/A N/A Zaim [27] 2005 489x382 789MHz 12 sec Badiei et al [28] 2006 480x640 P4 -1.7 GHZ 25.35 sec Zaim et al [29] 2007 489x382 N/A N/A Cosio [30] 2008 512x512 2 GHz 14 min Yan et al [31] 2010 640x480 Core 2 1.86GHz 0.3 sec (C++) Ghose et al [33] 2011 Markov Random Field (MRF) theory is utilized in order to strengthen the boundary edges and to remove the micro-calcifications inside the prostate gland. The probability distribution parameters are obtained from Expectation Maximization algorithm.…”
Section: Overlap (Ov) and Overlap Error (Oe)mentioning
confidence: 99%
“…Further, graph-based algorithms have been added to the current methodologies. Ghose et al suggested a scheme that incorporates the graph-cut (GC) algorithm into a Bayesian framework for automated initialization and parametric models (Ghose et al 2011). This scheme, however, involves a number of intermediate steps, which reduce the robustness of the segmentation and the ability to optimize the parameters.…”
Section: Introductionmentioning
confidence: 99%